100% tevredenheidsgarantie Direct beschikbaar na je betaling Lees online óf als PDF Geen vaste maandelijkse kosten
logo-home
SOLUTION MANUAL for Introduction to Probability Models 12th Edition by Ross Sheldon. | All Chapters 1-12 €26,99
In winkelwagen

Tentamen (uitwerkingen)

SOLUTION MANUAL for Introduction to Probability Models 12th Edition by Ross Sheldon. | All Chapters 1-12

 0 keer verkocht
  • Vak
  • Introduction to Probability Models 12th Edition
  • Instelling
  • Introduction To Probability Models 12th Edition
  • Boek

SOLUTION MANUAL for Introduction to Probability Models 12th Edition by Ross Sheldon. ISBN 3476, ISBN-13 978-9.TABLE OF CONTENTS_ 1. Introduction to Probability Theory 2. Random Variables 3. Conditional Probability and Conditional Expectation 4. Markov Chains 5. The Exponential Distribution and the ...

[Meer zien]

Voorbeeld 4 van de 205  pagina's

  • 4 september 2023
  • 205
  • 2023/2024
  • Tentamen (uitwerkingen)
  • Vragen en antwoorden
  • Introduction to Probability Models 12th Edition
  • Introduction to Probability Models 12th Edition
avatar-seller
, Solutions Manual For
Introduction to Probability Models 12th
Edition By Sheldon M. Ross




Chapter 1
1. S = {(R, R), (R, G), (R, B), (G, R), (G, G), (G, B), (B, R), (B, G), (B, B)}
The probability of each point in S is 1/9.
2. S = {(R, G), (R, B), (G, R), (G, B), (B, R), (B, G)}
3. S = {(e1 , e2 , . . . , en ), n ≥ 2} where ei ∈(heads, tails}. In addition, en = en−1 =
heads and for i = 1, . . . , n − 2 if ei = heads, then ei+1 = tails.
P{4 tosses} = P{(t, t, h, h)} + P{(h, t, h, h)}
 4
1 1
=2 =
2 8
4. (a) F(E ∪ G)c = F E c G c
(b) E F G c
(c) E ∪ F ∪ G
(d) E F ∪ E G ∪ F G
(e) E F G
(f) (E ∪ F ∪ G)c = E c F c G c
(g) (E F)c (E G)c (F G)c
(h) (E F G)c
5. 43 . If he wins, he only wins $1, while if he loses, he loses $3.
6. If E(F ∪ G) occurs, then E occurs and either F or G occur; therefore, either E F
or E G occurs and so
E(F ∪ G) ⊂ E F ∪ E G

,2 Introduction to Probability Models


Similarly, if E F ∪ E G occurs, then either E F or E G occurs. Thus, E occurs and
either F or G occurs; and so E(F ∪ G) occurs. Hence,
E F ∪ E G ⊂ E(F ∪ G)
which together with the reverse inequality proves the result.
7. If (E ∪ F)c occurs, then E ∪ F does not occur, and so E does not occur (and so E c
does); F does not occur (and so F c does) and thus E c and F c both occur. Hence,
(E ∪ F)c ⊂ E c F c
If E c F c occurs, then E c occurs (and so E does not), and F c occurs (and so F does
not). Hence, neither E or F occurs and thus (E ∪ F)c does. Thus,
E c F c ⊂ (E ∪ F)c
and the result follows.
8. 1 ≥ P(E ∪ F) = P(E) + P(F) − P(E F)
9. F = E ∪ F E c , implying since E and F E c are disjoint that P(F) = P(E) +
P(F E)c .
10. Either by induction or use
n
∪ E i = E 1 ∪ E 1c E 2 ∪ E 1c E 2c E 3 ∪ · · · ∪ E 1c · · · E n−1
c
En
1

and as each of the terms on the right side are mutually exclusive:
P( ∪ E i ) = P(E 1 ) + P(E 1c E 2 ) + P(E 1c E 2c E 3 ) + · · ·
i
+ P(E 1c · · · E n−1
c
En )
≤ P(E 1 ) + P(E 2 ) + · · · + P(E n ) (why?)

i−1
36 , i = 2, . . . , 7
11. P{sum is i} = 13−i
36 ,i = 8, . . . , 12
12. Either use hint or condition on initial outcome as:
P{E before F}
= P{E before F|initial outcome is E}P(E)
+ P{E before F|initial outcome is F}P(F)
+ P{E before F|initial outcome neither E or F}[1 − P(E) − P(F)]
= 1 · P(E) + 0 · P(F) + P{E before F}
= [1 − P(E) − P(F)]
P(E)
Therefore, P{E before F} = P(E)+P(F)
13. Condition an initial toss
12

P{win} = P{win|throw i}P{throw i}
i=2

, Instructor’s Manual to Accompany 3


Now,
P{win|throw i} = P{i before 7}


⎪ 0 i = 2, 12

⎪ i −1

⎨ i = 3, . . . , 6
= 5+1

⎪ 1 i = 7, 11

⎪ 13 − i

⎩ i = 8, . . . , 10
19 − 1
where above is obtained by using Problems 11 and 12.
P{win} ≈ .49.


14. P{ A wins} = P{ A wins on (2n + 1)st toss}
n=0
∞
= (1 − P)2n P
n=0


=P [(1 − P)2 ]n
n=0
1
=P
1 − (1 − P)2
P
=
2P − P 2
1
=
2− P
P{B wins} = 1 − P{ A wins}
1− P
=
2− P
16. P(E ∪ F) = P(E ∪ F E c )
= P(E) + P(F E c )
since E and F E c are disjoint. Also,
P(E) = P(F E ∪ F E c )
= P(F E) + P(F E c ) by disjointness
Hence,
P(E ∪ F) = P(E) + P(F) − P(E F)
17. Prob{end} = 1 − Prob{continue}
= 1 − P({H, H, H } ∪ {T, T, T })
= 1 − [Prob(H, H, H ) + Prob(T, T, T )].

Dit zijn jouw voordelen als je samenvattingen koopt bij Stuvia:

Bewezen kwaliteit door reviews

Bewezen kwaliteit door reviews

Studenten hebben al meer dan 850.000 samenvattingen beoordeeld. Zo weet jij zeker dat je de beste keuze maakt!

In een paar klikken geregeld

In een paar klikken geregeld

Geen gedoe — betaal gewoon eenmalig met iDeal, creditcard of je Stuvia-tegoed en je bent klaar. Geen abonnement nodig.

Direct to-the-point

Direct to-the-point

Studenten maken samenvattingen voor studenten. Dat betekent: actuele inhoud waar jij écht wat aan hebt. Geen overbodige details!

Veelgestelde vragen

Wat krijg ik als ik dit document koop?

Je krijgt een PDF, die direct beschikbaar is na je aankoop. Het gekochte document is altijd, overal en oneindig toegankelijk via je profiel.

Tevredenheidsgarantie: hoe werkt dat?

Onze tevredenheidsgarantie zorgt ervoor dat je altijd een studiedocument vindt dat goed bij je past. Je vult een formulier in en onze klantenservice regelt de rest.

Van wie koop ik deze samenvatting?

Stuvia is een marktplaats, je koop dit document dus niet van ons, maar van verkoper AcademiContent. Stuvia faciliteert de betaling aan de verkoper.

Zit ik meteen vast aan een abonnement?

Nee, je koopt alleen deze samenvatting voor €26,99. Je zit daarna nergens aan vast.

Is Stuvia te vertrouwen?

4,6 sterren op Google & Trustpilot (+1000 reviews)

Afgelopen 30 dagen zijn er 69052 samenvattingen verkocht

Opgericht in 2010, al 15 jaar dé plek om samenvattingen te kopen

Begin nu gratis
€26,99
  • (0)
In winkelwagen
Toegevoegd